PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Purnomo, Bambang Raditiya; Hasanah, Nur (J-MACC : journal of management and accounting, 2023)
This study aims to analyze the effect of work discipline and work environment on employee performance through job satisfaction as an intervening variable. The object of research is the employees of PT. Wahana Kreasi Ultima Surabaya with a population of 35 people. The method used in this study is a quantitative research method. The analysis technique used is the Partial Least Square (PLS) technique with validity testing, reliability testing, and hypothesis testing. The results of the study are : (1) work discipline has a significant effect on job satisfaction, (2) The work environment has a significant effect on job satisfaction, (3) Work discipline has a significant effect on employee performance, (4) The work environment has a t significant effect on employee performance, (5) Job satisfaction has a significant effect on employee performance, (6) Work discipline has a significant effect on employee performance through job satisfaction, (7) The work environment has a significant effect on employee performance through job satisfaction